2021
DOI: 10.4081/ejtm.2022.10271
|View full text |Cite
|
Sign up to set email alerts
|

Existential therapy versus acceptance and commitment therapy for feelings of loneliness and irrational beliefs in male prisoners

Abstract: Today’s people live in a society with many dangers to their peace and security. The effectiveness of different therapies in psychological variables needs to be evaluated to reach the most precise therapies based on research evidence. This study aimed to compare the effectiveness of existential therapy (ET) and acceptance and commitment therapy (ACT) in alleviating the loneliness and irrational beliefs of male prisoners. In the present quasi-experimental study, the statistical population consisted of all marrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The results of data analysis showed that, compared to the control group, the impacts of ET and ACT are significant on hope and irrational beliefs in male prisoners (with the greater effectiveness of ET in increasing hope compared to ACT). These findings were consistent with the studies of [15,20]. Concerning an increase in hope by ACT, people are taught to observe their thoughts and feelings without judgment as simple mental events.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of data analysis showed that, compared to the control group, the impacts of ET and ACT are significant on hope and irrational beliefs in male prisoners (with the greater effectiveness of ET in increasing hope compared to ACT). These findings were consistent with the studies of [15,20]. Concerning an increase in hope by ACT, people are taught to observe their thoughts and feelings without judgment as simple mental events.…”
Section: Discussionsupporting
confidence: 92%
“…It helps people accept their problems to understand their lives better and take responsibility to continue living. If the quality of life is reduced, the person won't take responsibility and blame others that can affect their lives [15]. Furthermore, the results of data analysis showed that there was no difference in the effectiveness of ET and ACT on irrational beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations